(untitled) (Research Journal on Multi-disciplinary Issues, 2026)
One of the most popular edible oils globally is the sunflower oil which has gained popularity especially in Nepal due to its lightness and taste and the ability to attain high smoke point without burning. The big downside, it contains a lot of polyunsaturated fats and this implies that it spoils quickly when we store or ship it. There was tested the quality of the three brands of sunflower oils namely Nilkamal, Pakwan, and Bigul that were sold at Lahan market in the Siraha District, Nepal by titration method and data analysis were carried out in triplicate manor where it is statistically treated using one-way ANOVA (p < 0.05).The acid value, saponification value, iodine value, and peroxide value were measured and the results compared among the brands. The acid values were between 0.18 and 0.32 mg/g KOH, saponification values were between 188.3 and 194.2 mg/g KOH, iodine values were 132.4 to 137.5 g/kg of I2, and peroxide values were 2.3 to 3.5 meq O2/kg. All the figures we obtained were within the scope of Codex Alimentarius and FAO/WHO, thus the oils are good quality and are not excessively oxidized. We also found that there were slight variations in the brands which demonstrate that good packaging, storage and checks are necessary to ensure that the oil remains fresh and safe to use by those who consume it.